Marketing at Patanjali Ayurved: Creating Value in a Herbal Way. (April 2020) - Pandey, Neeraj; Paul, Gaurav
On 9 October 2018, Baba Ramdev announced that Patanjali Ayurved Limited (PAL) would become the largest Fast-moving consumer goods (FMCG) organization in the world by 2025 (ET Bureau, 2018). PAL had created high visibility and awareness about its brands among consumers using the herbal and wellness positioning. The CAGR (compound annual growth rate) of 100 per cent since the last 4 years was an indicator of preference of herbal products by the consumers (Malviya & Bhushan, 2018). However, the competitors were launching various herbal product ranges to counter PAL. Baba Ramdev knew that consumer 'trust' in the brand building of herbal products was crucial. He was exploring various options for keeping the present trust intact.